The role of non-coding RNA on macrophage modification in tuberculosis infection. (December 2020) - Wang, Zhaohui; Xu, Hui; Wei, Zhenhong; Jia, Yanjuan; Wu, Yu; Qi, Xiaoming; Li, Yuanting; Gao, Xiaoling
Abstract: Tuberculosis (TB), a serious disease caused by Mycobacterium tuberculosis (Mtb), remains the world's top infectious killer. It is well-established that TB can circumvent the host's immune response for long-term survival. Macrophages serve as the major host cells for TB growth and persistence and their altered functions are critical for the response of the host defense against TB exposure (elimination, latency, reactivation, and bacillary dissemination). Noncoding RNAs are crucial posttranscriptional regulators of macrophage discrimination. Therefore, this review highlights the regulatory mechanism underlying the relationship between noncoding RNAs and macrophages in TB infection, which may facilitate the identification of potential therapeutic targets and effective diagnosis biomarkers for TB disease. Highlights: Macrophages persistence and their altered functions are critical for the response of the host defense against TB exposure. Noncoding RNAs are crucial posttranscriptional regulators of macrophage discrimination in tuberculosis infection. The regulatory mechanism between noncoding RNAs and macrophages in TB infection is complexed.